2016
DOI: 10.1007/s10578-016-0682-z
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of Depression Symptoms in Adolescence: Psychosocial Risk Factors and Outcomes

Abstract: Variations in symptom trajectories within a population may represent distinct groups with different etiologies and outcomes. This study aimed to identify subgroups of depression symptom trajectories in a sample of adolescents, and to describe psychosocial attributes of the different groups. In a longitudinal study, 243 adolescents (121 males and 122 females), were assessed using a battery of measures of temperament, psychopathology, and psychological and behavioral functioning. Four phases of data collection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 88 publications
4
59
0
3
Order By: Relevance
“…Ellis et al ( 2017 ) reviewed 18 studies and found that multiple trajectories of depressive symptoms, primarily three (e.g., Chaiton et al 2013 ; Diamantopoulou et al 2011 ; Mezulis et al 2014 ; Yaroslavsky et al 2013 ) or four (e.g., Ellis et al 2017 ; Reinke et al 2012 ; Stoolmiller et al 2005 ; Vannucci and Ohannessian 2017 ) provided best model fit. A common trajectory across all of these studies was a large group with stable and low levels of depressive symptoms, often accompanied by groups with moderate or high numbers of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Ellis et al ( 2017 ) reviewed 18 studies and found that multiple trajectories of depressive symptoms, primarily three (e.g., Chaiton et al 2013 ; Diamantopoulou et al 2011 ; Mezulis et al 2014 ; Yaroslavsky et al 2013 ) or four (e.g., Ellis et al 2017 ; Reinke et al 2012 ; Stoolmiller et al 2005 ; Vannucci and Ohannessian 2017 ) provided best model fit. A common trajectory across all of these studies was a large group with stable and low levels of depressive symptoms, often accompanied by groups with moderate or high numbers of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this body of work has shown that subtyping depression by its developmental trajectory can help identify the biological and environmental factors that shape the course of depressive symptoms over time (Ellis et al, 2017).…”
Section: Most Of Them Have Characterized Between Three and Six Primarmentioning
confidence: 99%
“…As such, more recent longitudinal studies have sought to model this time-dependent heterogeneity in depressive symptoms (as well as internalizing symptoms more broadly) by classifying individuals into subgroups based on their symptom trajectories over time. These studies have prospectively and repeatedly assessed depressive symptoms across an average of 3-6 years of development (Ellis et al, 2017); only a few include participants under 10 years old (Dekker et al, 2007;Kwong et al, 2019;Rice et al, 2018;Whalen, Sylvester, & Luby, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, as Pender (1996) points out, it includes cognition and social support (Wu, Pender, & Noureddine, 2015). In addition, several investigations highlight the role played by the family in both health and risk prevention (Cuffe, McKeown, Addy, & Garrison, 2005;Fatori, Bordin, Curto, & De Paula, 2013;Ellis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%